Use of Factor Analysis Scores in Multiple Regression Model for Estimation of Body Weight from Some Body Measurement in Muscovy Duck - Ogah, D.M.; Alaga, A.A.; Momoh, M.O. (International Journal of Poultry Science, 2009)
Factor and multiple regression analysis were carried out on morphological traits (body length, body width, bill length, bill width, bill height, shank length, body height, head length, head width, neck length, wing length, chest circumference and body weight) of male and female muscovy ducks. Obvious sexual dimorphism was exhibited between sexes, relationship between body measurement and body weight were examined through factor and multiple linear regression analysis. Three factors had positive significant effect on body weight of the male muscovy representing size and shape while only one factor had positive relationship with body weight in female, accounting for 84.2% and 63.5% of variation in body weight for male and female respectively. The result reveals that body measurements can be better selected for improvement in weight for male muscovy than for females.